PAX4 Gene Transfer Induces α-to-β Cell Phenotypic Conversion and Confers Therapeutic Benefits for Diabetes Treatment - Zhang, Yanqing (Mol Ther, 2016)
The transcription factor Pax4 plays a critical role in the determination of α- versus β-cell lineage during endocrine pancreas development. In this study, we explored whether Pax4 gene transfer into α-cells could convert them into functional β-cells and thus provide therapeutic benefits for insulin-deficient diabetes. We found that Pax4 delivered by adenoviral vector, Ad5.Pax4, induced insulin expression and reduced glucagon expression in αTC1.9 cells. More importantly, these cells exhibited glucose-stimulated insulin secretion, a key feature of functional β-cells. When injected into streptozotocin-induced diabetic mice, Pax4-treated αTC1.9 cells significantly reduced blood glucose, and the mice showed better glucose tolerance, supporting that Pax4 gene transfer into αTC1.9 cells resulted in the formation of functional β-cells. Furthermore, treatment of primary human islets with Ad5.Pax4 resulted in significantly improved β-cell function. Detection of glucagon(+)/Pax4(+)/Insulin(+) cells argued for Pax4-induced α-to-β cell transitioning. This was further supported by quantification of glucagon and insulin bi-hormonal cells, which was significantly higher in Pax4-treated islets than in controls. Finally, direct administration of Ad5.Pax4 into the pancreas of insulin-deficient mice ameliorated hyperglycemia. Taken together, our data demonstrate that manipulating Pax4 gene expression represents a viable therapeutic strategy for the treatment of insulin deficient diabetes.